The effect of speleothem surface slope on the remanent magnetic inclination. Issue 6 (29th June 2017) - Ponte, J. M.; Font, E.; Veiga‐Pires, C.; Hillaire‐Marcel, C.; Ghaleb, B.
Abstract: Speleothems are of interest for high‐resolution reconstruction of the Earth's magnetic field. However, little is known about the influence of speleothem morphologies on their natural remanent magnetization (NRM) record. Here we report on a high‐resolution paleomagnetic study of a dome‐shaped speleothem of middle Holocene age from southern Portugal, with special attention to the anisotropy of magnetic susceptibility (AMS) and anisotropy of anhysteretic remanent magnetization (AARM). To assess the potential influence of the slope of the speleothem surface on the recorded remanent magnetization, we compare magnetic directions and AMS and AARM fabrics from subhorizontal to gradually subvertical calcite growth layers collected in a transversal cross section of the speleothem. A linear correlation is observed between magnetic inclinations, calcite laminae slope, and AARM k 1 inclination. The AMS fabric is mostly controlled by calcite crystals, with direction of the minimum axes ( k 3 ) perpendicular to laminae growth. Magnetic inclinations recorded in inclined and vertical calcite growth layers are underestimated when compared to a global paleosecular variation (PSV) model. After extrapolating magnetic inclinations to the horizontal, the corrected data better fit the PSV model but are still lower than the predicted magnetic inclinations, suggesting that inclination shallowing affects the entire speleothem. We suggest that speleothem morphology exerts a critical role on the magnetic inclination recording, which is controlled by the Earth's magnetic field but also influenced by particle rolling along the sloping surfaces. These observations open new avenues for reconstructing high‐resolution paleomagnetic secular variation records from speleothems and provide new insights into their NRM acquisition mechanisms. Key Points: Magnetic inclinations recorded in the studied speleothem are biased by the slope of the speleothem surface Magnetic inclination is controlled by the ambient magnetic field but hence influenced by particle rolling down the speleothem surface We suggest that future studies of paleomagnetism in speleothems only consider data obtained from horizontal calcite layers